Semantics in Natural Language Processing and Language Teaching - Ounu Sukaton (ELS Journal on Interdisciplinary Studies in Humanities, 2019)
Semantics is one of the key elements in the study of language. This article’s main objective is to describe and evaluate how semantic theories are implemented in the field of Natural Language Processing as well as Language Teaching. There are two branches of semantic theories that this article focuses on: Formal Semantics and Natural Semantic Metalanguage. The strengths and weaknesses of the theories mentioned are discussed. The most versatile theory is suggested along with future improvements.